Evaluation of anthropogenic disturbance on African clawless otter (Aonyx capensis) physiological stress, behaviour, and population density using non-invasive methods - Ganswindt, Andre (University of Pretoria, 2024)
Dissertation (MSc (Zoology))--University of Pretoria, 2019.